Enlivening the senses: engaging sight and sound to (re)consider the hidden narratives of academics in the histories of university education. Issue 2 (4th March 2018) - Manathunga, Catherine; Selkrig, Mark; Baker, Alison
Abstract: This article interrogates the construction of a visual and sound installation that juxtaposes contemporary material with historical artefacts regarding academic work to offer an aesthetic mode of interruption in explorations of academic voice in university histories and in the contemporary university. Drawing upon Foucauldian histories of the present (particularly genealogy), this installation combines text, images and sound to take audiences on an emotive journey of the university. As historical research increasingly takes on an aesthetic and sensual turn, moving beyond content and context to consider other forms of representation, the article draws on theories concerning the functions of art and the semiotics involved when we engage with art to explore the emotional dimensions of academic work. Art in story and story in art methodologies are used to situate attempts at engaging in aural and visual ways of knowing time and place to (re)consider academics' silenced historical and contemporary narratives.